Unitarianism dalam Ajaran kristian: Idea, Sejarah dan Perkembangan - bin Ahmad, Mahmud; Mohd Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 2009)
Unitarianism is one of the Christian sects or Christian church which highlighted the Oneness of God and there is no partner with Him; and regard Jesus as a created being; as a messenger of God; has lower position compared with God and he does not have the substance and nature of deity (divinity). The existence of the Unitarianism is regarded as ’reformation movement’ in the teachings of Christianity. They and the fractions of this group is now enganging a rapid missionary activities throughout the world including Malaysia. Their approach of the doctrine of Divinity is found quite similar to the Islamic da`wah in emphasizing the Unity of God. Congregations and meetings held by them were attracted many Christians to participate in their belief. This phenomeNon is forcing us to see the extent of understanding or perception of this trend of ’Jesus.